Neoliberalism, internationalisation and higher education: connections, contradictions and alternatives. Issue 2 (4th March 2019) - Bamberger, Annette; Morris, Paul; Yemini, Miri
ABSTRACT: We explore the role of neoliberalism within portrayals of internationalisation in higher education (HE). Through an analysis of four features of internationalisation, we suggest that they embody a complex entanglement of neoliberal categories and assumptions with other, primarily progressive humanitarian ideals. This framing of internationalisation has three affects. One, humanitarian ideals coupled with neoliberal categories normalise inequalities, turning internationalisation into a meritocratic global race, focusing on celebrating the possibility of the few who can achieve, instead of the embedded inequalities within the system, which disadvantage the many. Two, this allows neoliberal practices to be advanced through the discourse of internationalisation and its association with progressive humanitarian values. Three, this neoliberal framing does not explain the nature of internationalisation of HE in many nations; we demonstrate this by analysing internationalisation in China, Israel and Cuba. We suggest that internationalisation in HE cannot be adequately explained by analyses which rely on neoliberalism.